2017
DOI: 10.3390/nu9090966
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Therapeutic Strategies for Cardiovascular Conditions Associated with Oxidative Stress

Abstract: Oxidative stress (OS) refers to the imbalance between the generation of reactive oxygen species (ROS) and the ability to scavenge these ROS by endogenous antioxidant systems, where ROS overwhelms the antioxidant capacity. Excessive presence of ROS results in irreversible damage to cell membranes, DNA, and other cellular structures by oxidizing lipids, proteins, and nucleic acids. Oxidative stress plays a crucial role in the pathogenesis of cardiovascular diseases related to hypoxia, cardiotoxicity and ischemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(110 citation statements)
references
References 167 publications
(177 reference statements)
6
100
0
4
Order By: Relevance
“…Several studies demonstrated that cardiac hypertrophy is caused by switching of adult alpha myosin heavy chain (α-MHC, known as Myh6) to fetal beta myosin heavy chain (β-MHC, known as Myh7) gene expression. In experimental studies, deletion of miRNA-208a, which is encoded in the intron of the Myh6 gene, leads to the decreased expression of the Myh7 gene in response to stress and to hypertrophy [88,98]. These results were confirmed in the study of Rawal et al, where inhibition of miRNA-208a hampers the activation of β-MHC and hypertrophic response [99].…”
Section: Cardiac Hypertrophymentioning
confidence: 70%
See 1 more Smart Citation
“…Several studies demonstrated that cardiac hypertrophy is caused by switching of adult alpha myosin heavy chain (α-MHC, known as Myh6) to fetal beta myosin heavy chain (β-MHC, known as Myh7) gene expression. In experimental studies, deletion of miRNA-208a, which is encoded in the intron of the Myh6 gene, leads to the decreased expression of the Myh7 gene in response to stress and to hypertrophy [88,98]. These results were confirmed in the study of Rawal et al, where inhibition of miRNA-208a hampers the activation of β-MHC and hypertrophic response [99].…”
Section: Cardiac Hypertrophymentioning
confidence: 70%
“…Oxidative stress plays a crucial role in many cardiovascular diseases, like hypoxia, ischemia/reperfusion injury, or heart failure [88]. As mentioned before, intracellular ROS are formed in normal conditions as the result of normal mitochondrial respiration, but ROS are also produced during reperfusion in hypoxic tissue and in association with infection and inflammation, leading to pathological conditions of the heart [88,89]. One of the effects of ROS accumulation in cardiomyocytes is a different expression of noncoding RNAs (ncRNAs), subsequently contributing to cell apoptosis and heart pathology.…”
Section: Mirna In Oxidative-stress-induced Heart Diseasesmentioning
confidence: 99%
“…The control of oxidative stress caused by these reasons is thought to be effective in the prophylaxis of uterine fibroids. Nowadays, it is known that antioxidant agents and related diet products contribute to the process and have a role in treatment in many pathological conditions (36)(37)(38). Considering all these mechanisms, the role of antioxidant agents in the treatment of uterine fibroids can be discussed.…”
Section: Inhibition Of Oxidative Stress In the Cell By Amino Acids Anmentioning
confidence: 99%
“…CAR is a third‐generation neurohormonal antagonist with multiple activities and it blocks both α‐, β 1 ‐ and β 2 ‐adrenergic receptors. In addition to its well‐known properties, CAR has a number of ancillary activities, including antioxidant (Farías et al, ; Areti, Komirishetty, & Kumar, ), anti‐inflammatory and anti‐apoptotic properties, and appears to reduce DOX cardiotoxicity (Matsui et al, ; Santos, Moreno, Leino, Froberg, & Wallace, ). The antioxidant activity of CAR has been widely implicated in enhancing the free radical‐mediated toxicity caused by DOX, diminishing the DOX‐induced negative impact on systolic blood pressure (BP) and left ventricular fractional shortening (Fazio et al, ), and on increased lipid peroxidation (Matsui et al, ; Oliveira et al, ).…”
Section: Introductionmentioning
confidence: 99%